“Everyone Needs a Friend Sometimes” – Social Predictors of Long-Term Remission In First Episode Psychosis - Bjornestad, Jone; Joa, Inge; Larsen, Tor K.; Langeveld, Johannes; Davidson, Larry; ten Velden Hegelstad, Wenche; Anda, Liss G.; Veseth, Marius; Melle, Ingrid; Johannessen, Jan O.; Bronnick, Kolbjorn (Frontiers in Psychology, 2016)
Background Predictors of long-term symptomatic remission are crucial to the successful tailoring of treatment in first episode psychosis. There is lack of studies distinguishing the predictive effects of different social factors. This prevents a valid evaluating of their independent effects. Objectives To test specific social baseline predictors of long-term remission. We hypothesized that first, satisfaction with social relations predicts remission; second, that frequency of social interaction predicts remission; and third, that the effect of friend relationship satisfaction and frequency will be greater than that of family relations satisfaction and frequency. Material and Methods A sample of first episode psychosis (n=186) completed baseline measures of social functioning, as well as clinical assessments. We compared groups of remitted and non-remitted individuals using generalized estimating equations analyses. Results Frequency of social interaction with friends was a significant positive predictor of remission over a two-year period. Neither global perceived social satisfaction nor frequency of family interaction showed significant effects. Conclusions The study findings are of particular clinical importance since frequency of friendship interaction is a possibly malleable factor. Frequency of interaction could be affected through behavioral modification and therapy already from an early stage in the course, and thus increase remission rates. Keywords First-Episode Psychosis, Schizophrenia, Social factors, Baseline predictors, Long-term remission.